ECOLOGICAL STUDY OF ACCIDENTS CAUSED BY CROTALUS SP SNAKES IN BRAZIL BETWEEN 2010 AND 2023 - Faleiros, Concepción Matheus Carvalho; da Silva, Livia Maria Bortolotti; Pires, Julia da Palma; Custodio, Rodrigo José; Custodio, Viviane Imaculada do Carmo (Seven Editora, 2025)
Introduction: Accidents caused by venomous snakes represent an important challenge for public health, especially in rural regions of countries with tropical climates. It is estimated that, annually, there are about 5 million snakebites in the world, resulting in approximately 100 thousand deaths. In Brazil, the genera Bothrops and Crotalus stand out, the latter being associated with higher lethality and severe clinical manifestations, such as neurotoxicity, myotoxicity, and acute renal failure. In addition to the clinical repercussions, these accidents have relevant economic and social impacts, especially because they affect individuals of working age in rural areas. Early Goal: To investigate the epidemiological profile of accidents caused by snakes of the genus Crotalus in Brazil between 2010 and 2023, analyzing mortality, regional distribution, seasonal variation, sex, age group, and anatomical site of the bite, in order to identify relevant patterns for surveillance and public health. Methodology: This is an ecological, descriptive and retrospective study, based on secondary data extracted from the Notifiable Diseases Information System (SINAN/DATASUS). All cases registered in the country between 2010 and 2023 were included. The variables analyzed included: absolute number of cases and deaths, mortality rate, regional distribution, seasonality, gender, age group, and location of the bite. Statistical analysis was performed by means of descriptive statistics, using absolute and relative frequencies, with processing in Microsoft Excel. Results and discussion: There was a continuous growth in the number of notified snakebites, from 124,920 cases in 2010 to 340,819 in 2023. In total, 296,475 botropic and 34,080 crotalic accidents were recorded, with mortality rates of 0.42% and 0.95%, respectively. Crotalic cases were more concentrated in the Northeast (37.8%) and Southeast (35.2%) regions, being more frequent in the hot and rainy months (January to March), which accounted for 34% of the notifications. There was a predominance of males (80%) and adults of working age (20 to 59 years: 22,209 cases), which reflects the greater occupational exposure in agricultural activities. The bites occurred mainly on the lower limbs (65.2%), followed by the upper limbs (20.2%), often during the inadvertent handling of the animals in the rural work environment. These epidemiological variations appear to be associated with environmental, climatic, and occupational factors that increase the risk of contact with snakes. Conclusions: Crotalic accidents predominantly occurred adult men living in rural areas, especially in the rainy months, with more frequent injuries in the lower limbs. These findings reinforce the importance of public policies aimed at prevention, such as the provision of personal protective equipment (PPE) and the training of health teams for timely diagnosis and treatment. Among the limitations of the study, the use of secondary data, subject to underreporting and lack of detailed clinical information, stands out. Even so, the results contribute to guide future research on environmental determinants and the effectiveness of serum therapy in different regions of the country.DOI: https://doi.org/10.56238/sevened2025.036-099